Exploring Ibn Taimiyyah’s Model of Psychological Resilience in the Light of Islam and Psychology - Sayema Zulfeqar (International Journal of Emerging Issues in Islamic Studies, 2024)
The concept of psychological resilience and what makes human beings bounce back from adversities has always intrigued philosophers and theologians in the past and continues to fascinate modern psychology. It has been claimed by Western psychology that Emmy Werner, an American developmental psychologist, was one of the earliest scientists to study psychological resilience in the 1980s. In this paper, the author aims to reveal an even earlier presentation of what we understand today as resilience, based on the 12th-century work, The Principle of Patience, written by Ibn Taimiyyah during the golden age of Islam. Discovery of this manuscript reveals that Ibn Taimiyyah’s twenty recommendations for fostering psychological resilience parallel modern-day therapeutic interventions employed in Dialectical Behavioural Therapy (DBT) and Cognitive Behavioral Therapy (CBT). The research also reveals that Ibn Taimiyyah should be credited for identifying acceptance, patience, and forgiveness as key tools for building psychological resilience and highlighting their positive impact on physical and mental health, nearly centuries before modern psychology.